2022
DOI: 10.1111/gbb.12794
|View full text |Cite
|
Sign up to set email alerts
|

Visuo‐spatial learning and memory impairments in the 5xFAD mouse model of Alzheimer's disease: Effects of age, sex, albinism, and motor impairments

Abstract: The 5xFAD mouse model of Alzheimer's disease (AD) rapidly develops AD‐related neuro‐behavioral pathology. Learning and memory impairments in 5xFAD mice, however, are not always replicated and the size of impairments varies considerably across studies. To examine possible sources of this variability, we analyzed the effects of age, sex, albinism due to background genes (Tyrc, Oca2p) and motor impairment on learning and memory performance of wild type and 5xFAD mice on the Morris water maze, from 3 to 15 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 140 publications
(375 reference statements)
4
28
0
Order By: Relevance
“…In reversal probe, transgenic females, independently of treatment, showed higher latencies to find the new platform compared to old one, which could indicate a sex‐dependent impaired cognitive flexibility as reported in different protocols for the reversal probe for 3‐month‐old 5xFAD males 45 and 3‐15‐month old 5xFAD animals of both sexes. 46 PWZ‐029 vs. control‐treated non‐transgenic males showed an enhanced exploration of the old platform, as reflected in the number of entries in the old platform zone and latency to find the old platform, which could be an indicator of cognitive perseverance. 47 …”
Section: Discussionmentioning
confidence: 97%
“…In reversal probe, transgenic females, independently of treatment, showed higher latencies to find the new platform compared to old one, which could indicate a sex‐dependent impaired cognitive flexibility as reported in different protocols for the reversal probe for 3‐month‐old 5xFAD males 45 and 3‐15‐month old 5xFAD animals of both sexes. 46 PWZ‐029 vs. control‐treated non‐transgenic males showed an enhanced exploration of the old platform, as reflected in the number of entries in the old platform zone and latency to find the old platform, which could be an indicator of cognitive perseverance. 47 …”
Section: Discussionmentioning
confidence: 97%
“…In hepatic cells, during normal aging, IGF2 directly interacts with growth hormone to increase its transcriptional activity for promotion of somatic growth and the regulation of metabolism 92 . The reduction of IGF2 levels in the cerebrum and liver may help to explain the pathological weight loss and cognitive deficits seen in the 5xFAD mice 18 , 60 . Higher IGF2 levels in the young WT mice may be a part of normal development, protecting developing blood cells against oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore compared Aβ 42 and IGF2 levels in cerebrum, liver, and blood plasma from 6- and 12-month-old, male and female 5xFAD mice with age- and sex-matched B6SJLF1/J wild-type (WT) mice. The 5xFAD mice show initial weight loss and cognitive deficits at 6-months of age 18 , 60 , with severe deficits and increased mortality by 12-months of age, especially in males 61 , providing a useful model to study age-related expression patterns of Igf2 and IGF2 in central, peripheral, and circulatory systems in response to Aβ accumulation. To determine whether the findings from the mouse model translated to human disease, we compared Igf2 epigenetic regulation in frontal cortex from aged humans diagnosed with AD and non-AD controls.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that various anxiety disorders and neurodegenerative diseases such as Alzheimer’s disease (AD) have a higher incidence in females [ 26 , 27 ]. Alzheimer’s disease is usually related to higher anxiety levels [ 27 ] and spatial memory impairment [ 28 ]. Several studies have demonstrated that gender factors contribute to phenotypic differences [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%